Correction: High-surface-area mesoporous TiO2 microspheres via one-step nanoparticle self-assembly for enhanced lithium-ion storage. Issue 48 (19th November 2015) - Wang, Hsin-Yi; Chen, Jiazang; Hy, Sunny; Yu, Linghui; Xu, Zhichuan; Liu, Bin
Abstract : Correction for 'High-surface-area mesoporous TiO2 microspheres via one-step nanoparticle self-assembly for enhanced lithium-ion storage' by Hsin-Yi Wang et al., Nanoscale, 2014, 6, 14926–14931.